Oral Acetazolamide Administration to Control Intraocular Pressure on First Day Post Phacoemulsification Surgery : Is It Necessary ? - Reinne Natali christine; Henricus Datu Respatika; Gilbert Simanjuntak (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2017)
Introduction : The incidence of early postoperative intraocular pressure (IOP) increase is reported to be 2.3–8.9% in phacoemulsification surgery. This increase typically peaks at 3–7 hours after surgery and persists during the first 24 hours. Although most eyes can tolerate the transient IOP elevation that occurs after cataract surgery, IOP spikes are potentially more dangerous if it persist. In order to minimize postoperative intraocular pressure (IOP) rise, routine medication by oral acetazolamide has been widely used among ophthalmologists. Objective of this study is to investigate the relationship between IOP changes on first day after phacoemulsification with administration of oral acetazolamide. Method : This is a descriptive study. The samples were include 50 patients diagnosed with cataract who underwent phacoemulsification surgery with intraocular lens implantatios. Samples were randomized divided into two groups. First group is patient who treated with 250 mg acetazolamide post operative and other group is untreated. All respondents must have no history of glaucoma or ocular hypertensive and attend follow up on the first day postoperative. IOP is measured with non-contact tonometer. Results : Mean age of respondents is 61  9.8 years old. Preoperative IOP mean is 18.04  3.6 mmHg and postoperative IOP mean is 18.58  6.9 mmHg. This study revealed that there is no significant relation between oral administration of acetazolamide and the lowering of intraocular pressure on first day post phacoemulsification(p = 0.2) Visual acuity pre operative and nuclear density of cataract are also no relationship with the IOP on first day postoperative (p = 0.2 ) Conclusion : The use of oral acetazolamide is not significantly related to the IOP on first day post phacoemulsification surgery.